A new genetic selection identifies essential residues in SecG, a component of the Escherichia coli protein export machinery. - Bost, S (1995)
The signal sequence of the murine serine protease inhibitor PAI-2 promotes alkaline phosphatase export to the E. coli periplasm. However, high level expression of this chimeric protein interferes with cell growth. Since most suppressors of this toxic phenotype map to secA and secY, growth arrest results from a defective interaction of the chimeric protein with the export machinery. We have characterized suppressors which map in secG, a newly defined gene of the export machinery. All single amino acid substitutions map to three adjacent codons. These secG mutants have a weak Sec phenotype, as determined by their effect on export mediated by wild-type and mutant signal sequences. Whilst a secG disruption allele also confers a weak Sec phenotype, it does not suppress the toxicity of the chimeric protein. This difference results from a selective effect of the secG suppressors on the kinetics of export mediated by the PAI-2 signal sequence. Using a malE signal sequence mutant, which has a Mal-phenotype in secG mutant strains, we have isolated extragenic Mal+ suppressors. Most suppressors map to secY, and several are allele-specific. Finally, SecG overexpression accelerates the kinetics of protein export, suggesting that there are two types of functional translocation complexes: with or without SecG.